Interactive Learning Media using Adobe Animate CC to Improve Students’ Learning Motivation and Mathematics Learning Outcomes - Wahyuliana, Nurfajar; Andrian, Dedek; Nofriyandi, Nofriyandi; Widiati, Indah (FKIP Universitas Lampung, 2023)
This study aims to apply digital learning media in the form of Adobe Animate CC in learning mathematics. This research is a quantitative research with a comparative approach to compare learning outcomes based on the application of interactive learning media Adobe Animate CC. The research population was all junior high schools in Bengkalis Regency, while the sample was a portion of the schools taken purposively according to the purpose of the research. The data collection tool is a learning achievement test and a checklist to observe student learning motivation in class while studying with Adobe Animate CC. Data analysis in this study used descriptive statistics, t-test and One Way Anova. The results of the analysis show that there are significant differences in student learning outcomes in the experimental class using Adobe Animate CC learning media and the control class using conventional learning. There were significant differences in learning motivation in the experimental class at the first meeting, second meeting, third meeting and fourth meeting. Adobe Animate CC learning media can improve learning outcomes and motivation of junior high school students in Bengkalis Regency, Riau Province.Keywords: digital learning media, learning outcomes, learning motivation.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp172-182